PHYTO-CONSTITUENTS AND ANTI-OXIDANT ACTIVITY OF THE PULP OF SNAKE TOMATO (TRICHOSANTHES CUCUMERINA L.) - Adebooye, C. O. (African Journal of Traditional, Complementary and Alternative Medicines, 2007)
The phyto-constituents and antioxidant activity of the fruit pulp of Trichosanthes cucumerina L. have not been reported in literature and were therefore studied. Two identified morphotypes of this plant (Morphotype I [V1] having long fruit with deep green background and white stripes; and Morphotype II [V2] having light green coloured long fruit) were used for the studies. The dry matter contents of the pulp of the V1 and V2 were 10.9 and 9.6 g/100g fresh weight (FW), while the ascorbic acid contents were 25.7 and 24.8 mg/100g fresh weight (FW), and lycopene contents were18.0 and 16.1 mg/100g FW, respectively. The total phenolics, total flavonoids and total ferric reducing antioxidant power (FRAP) of V2 were significantly higher (P< 0.05) than that of V1 by 46.8%, 78.0% and 26.2%, respectively. Bulk of the carotenoids is made up of lutein in the concentration of 15.6 and 18.4 mg/100g FW, for V1 and V2, respectively. The α-carotene contents were 10.3 and 10.7 mg/100g FW while the β-carotene contents were 2.4 and 2.8 mg/100g FW for V1 andV2, respectively. It is concluded from the results of this study that the two morphotypes of T. cucumerina possess valuable nutraceutical properties that can qualify them as viable substitute to the Solanaceous tomato.